Interstep compatibility of a model for the prebiotic synthesis of RNA consistent with Hadean natural history - Yuta Hirakawa; Hyo-Joong Kim; Yoshihiro Furukawa; Clay Abraham; Tzu-Wei Peng; Elisa Biondi; Steven A. Benner (Proceedings of the National Academy of Sciences, 2025)
Models for prebiotic syntheses often have many steps, each separately validated by laboratory experiments. The challenge then asks whether these steps work together in natural geological environments, absent human intervention. Here, we analyze a six-step Discontinuous Synthesis Model (DSM) for the prebiotic formation of RNA, proposed to be the first informational molecule to support Darwinian evolution, and life, on Earth and/or Mars. DSM requires that borate in multiple steps guide the formation of pentoses from simple carbohydrates and control phosphorylation, in all cases by binding adjacent HO-groups on key intermediates. However, adjacent HO-groups must react in two other steps, which borate might inhibit. Experiments here show that borate does not inhibit these two other steps, but rather facilitates them. This makes the six-step DSM a “no human intervention” route from simple precursors (1 to 3 carbons, 0 to 2 nitrogens) to oligomeric RNA with predominately 3’,5’-linkages at least 6 nucleotides long, but possibly much longer. The process i) exploits privileged chemistry in ii) intermittently irrigated aquifers constrained by basalt that iii) have borate iv) above a redox-neutral mantle v) having access to an atmosphere transiently reduced by a Vesta-sized impactor. In a possible coincidence, such an impact occurred most likely ca. 4.3 billion years ago (Ga), ~100 Mya before some molecular clocks date the divergence of the three kingdoms of life on Earth (4.2 Ga), and ca. 200 Mya before isotopically “light” carbon is reported in zircons dated at 4.1 Ga. This carbon may be the oldest trace of life ever proposed.